Penerapan Fast Fourier Transform Method Untuk Monitoring Tegangan Fluktuasi - Tauladan, Imam Suri; Hendri Novia Syamsir; Arif Gunawan (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
Based on PLN standards regulated in Minister of Energy and Mineral Resources Regulation No. 20 of 2020, changes in voltage on the network must be maintained within the voltage variation range of ±5% (Normal Voltage). Voltage is the change in voltage variations in a short time. Where the voltage change exceeds or below the standard voltage variation range, namely ±5% of the normal voltage. Based on IEEE Standard 1159-1995, the sag voltage is in the range of 10% -90% of the nominal voltage which lasts for 0.5 cycles. The voltage wave is in the range of 120% of the nominal voltage. Changes in voltage variations are caused by many factors such as large motor starting currents, uncontrolled load changes and short circuit current disturbances in the electric power system. The importance of maintaining voltage is a necessity because it is related to the reliability of an electric power system. For this reason, this research proposes "Application of the Fast Fourier Transform Method to Monitor Voltage Fluctuations" as a solution to power quality problems. To make it easier to process voltage (sinusoidal), the Fast Fourier Transform (FFT) method is needed. The FFT method algorithm is needed to convert the time domain into the frequency domain, so that it can simplify the monitoring system process. This research was implemented the FFT method for monitoring voltage fluctuations in no-load and load conditions. From the results, it can be concluded that inductive loads can affect voltage quality. This was proven when carrying out tests under load, from the results of the analysis there was a decrease in voltage (voltage SAG) of 10% (Vrms = 209.5 V; time duration 0.1436 s) and an increase in voltage (voltage swell) of 20.6% ( Vrms = 278.75 V; time duration 0.228 – 0.428 s).